Local commons and cross-effects of population and inequality on the local provision of environmental services (2004)
A farm-level and village level models are discussed and tested empirically using spatial data, for exploring the cross-effects between population density and land inequality in the "tragedy of the commons". Malthus himself argued that "An unfavourable distribution of produce, by prematurely diminishing the demand for labour, might retard the increase of food at an early period, in the same manner as if cultivation and population had been further advanced;" [Malthus (1830): pp. 239]. By exploring the farm and village level institutions and incentives for allocating land and labor to conservation or agriculture, the paper argues that inequality exacerbates the population pressure over the provision of environmental services, and that under more equal distribution of land, more sustainable technological adaptations may happen in which better farm and land-use practices emerge, decreasing the level of land degradation.